Reflections on Cultural Bias and Adaptation - Pargman, Daniel (Javnost-The Public, 1999)
"SvenskMud" (Swedish MUD) is an Internet-accessible Multi-User Domain (MUD) system but, in contrast to 99% of all Internet-accessible MUDs, SvenskMud is not a global community. Rather, SvenskMud is the first vernacular (i.e. non-English speaking) MUD in the world, and the only Swedish-speaking MUD in Sweden today. This article addresses four questions with regards to cultural attitudes and their relationship to computer-mediated communication (CMC) technologies: (1) How have American cultural attitudes (historically) shaped the development and use of CMC technologies? (2) How do today's cultural attitudes shape the implementation and use of CMC technologies? (3) How do cultural attitudes manifest themselves in the implementation and use of MUDs? (4) How do cultural attitudes manifest themselves in the implementation and use of SvenskMud?